New SCO development strategy: analysis of Russia’s interests - Seilkhan, Б.; Bukeshova, Г.К. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2022)
After the collapse of the Soviet Union, a new geopolitical situation arose, which gave rise to new threats, challenges, and problems, both on the regional and on world stage. The already heterogeneous Central Asia, as well as the neighborhood with Afghanistan, made us think about security and stability in the region. It was then that the historic decision was made to create the SCO. It is during this period that the US strategy toward post-Soviet Russia and the country of Central Asia is emerging. The strategy clearly saw the desire of the United States of America to distance new independent states from Russia, which recently were part of the USSR, all this happened against the background of maximum opposition to its renewed self-assertion in the region and in the world. The problems of cooperation in the field of security were a red thread in all the adopted documents, Russia itself adhered to this idea and insisted during its chairmanship in 2008-2009 and 2014- 2015. Further, Russia began to actively promote its interests against the background of the aggravation of relations with the West. It was Russia that initiated its expansion, as well as strengthening cooperation in issues of disarmament, settlement of international and regional problems, the peaceful use of outer space, information security, and the formation of a more equitable international financial structure. Thanks to Russia, such strong players as India and Pakistan, Belarus in observer status, and Azerbaijan, Armenia, Cambodia, and Nepal as dialogue partners were attracted to this organization.